2008
DOI: 10.1177/1938640007312316.
|View full text |Cite
|
Sign up to set email alerts
|

A Stepwise Approach to the Surgical Management of Severe Diabetic Foot Infections

Abstract: Foot infections are common among diabetic patients with ulceration and are a major cause of hospitalization and lower extremity amputation. Aggressive and emergent surgical intervention is essential in the face of life- or limb-threatening infection to achieve limb salvage and survival. Critical limb ischemia, neuropathy, and an impaired host complicate the treatment of a severe diabetic foot infection. A severe diabetic foot infection carries a 25% risk of major amputation. For this reason, surgery should be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 65 publications
0
12
0
2
Order By: Relevance
“…Various studies show that diabetic foot infection has the longest hospital stay as compared to other complications of diabetes [11,12]. We found that the most of the diabetic foot patients were hospitalized for about 2 weeks.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Various studies show that diabetic foot infection has the longest hospital stay as compared to other complications of diabetes [11,12]. We found that the most of the diabetic foot patients were hospitalized for about 2 weeks.…”
Section: Discussionmentioning
confidence: 94%
“…This diabetic complication is very difficult to treat if proper protocol is not followed [10][11][12]. However, most researchers agree that the management of this infection requires isolation and identification of microbial flora, appropriate antibiotic therapy according to the local sensitivity pattern, proper selection and identification of chronic complications and appropriate surgical intervention for this complication [7].…”
Section: Aimsmentioning
confidence: 99%
“…Direkt grafi, Amerikan Radyoloji Koleji'nin Uygunluk Kriterleri (21) listesine göre en uygun yöntem olarak kabul görse de, osteomiyelitin tanısında düşük duyarlılık ve özgüllüğe sahip olup, tutulum direkt grafi ile iki hafta sonra görülebilmektedir (13,22). Kemik demineralizasyonu, periost reaksiyonu ve kortikal destrüksiyonu tespit edebilir; ancak, bu bulguların direkt grafide görülebilmesi için, enfeksiyonun başlangıcından sonra 14 günlük bir süre geçmesi gereklidir.…”
Section: Radyolojikdeğerlendirmeunclassified
“…DA'da saptanan patolojilerde duyarlılık ve özgüllük oranı, sırasıyla, %90 ve %83 olup diğer yöntemlere oranla oldukça yüksektir (21,28). Osteomiyelit açısından, direkt grafi ve şüpheli durumlarda, MR görüntüleme önerilmektedir (13,29,30). Ancak, kemik ödemine neden olan cerrahi durumlarda özgüllüğü etkilenir (31).…”
Section: Manyetikrezonans(mr)unclassified
“…In diabetic foot with ulceration, infection is fairly common and is main reason for hospital admission [1]. Infection in diabetic foot is usually caused by direct spread from skin ulcer which leads to various pathologies affecting musculoskeletal structure.…”
Section: Introductionmentioning
confidence: 99%